INNOVATIVE COOLING SYSTEM: SOLAR-POWERED WATER SPRAYERS FOR CATTLE SHEDS IN TULUNGAGUNG REGENCY - Asrori, Asrori; Nugroho, Pipit Wahyu; Yudiyanto, Eko; Witono, Kris; Buwono, Haris Puspito; Hidayat, Mohammad Noor (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The Community Service (CS) project was implemented in Sumberingin Kidul Village, Ngunut District, Tulungagung Regency, East Java. The target beneficiary was UD. Arta Lumintu, a local SME engaged in beef cattle farming. The farm, established in 2017, was temporarily closed due to the Covid pandemic and resumed operation after a year. Key challenges included high temperatures (24-31°C) and humidity (74-77%), which negatively impacted cattle productivity and excessive electricity consumption for cattle shed operations. The project aimed to address these issues by installing a water spray system with a high-pressure pump and an off-grid solar power system. The system effectively reduces temperature and humidity in the sheds while minimizing electricity costs. The installation consists of a 540 Wp solar panel, a 1500 VA Smart inverter, a 100 Ah VRLA battery, and six pressurized water sprinkler points positioned in various areas of the cattle sheds, powered by a 350 W booster pump. This initiative improves farm efficiency, supports energy independence, and introduces smart farming technology to benefit local farmers.